Biodiversität und nachhaltige Landnutzung in Großschutzgebieten - Job, Hubert; Woltering, Manuel; Warner, Barbara; Heiland, Stefan; Jedicke, Eckhard; Meyer, Peter; Nienaber, Birte; Plieninger, Tobias; Pütz, Marco; Rannow, Sven; Ruschkowski, Eick von (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
Land-use systems and biodiversity in Germany can be investigated using the network of protected areas. This issue focuses on nature parks, national parks and biosphere reserves that are confronted with various problems related to competition for land and acceptance. The working group “Biodiversity and sustainable land use in protected areas” of the Academy for Spatial Research and Planning (ARL) has tackled this topic. This paper reviews the research questions that are debated in this special issue of “Raumforschung und Raumordnung”. These questions include the influence of different land-use systems on the state of ecosystem services, how the different types of protected areas should be evaluated in terms of their individual contributions to the conservation and development of biodiversity, the role played specifically by woods and forestry management with regard to biodiversity and sustainable land use, and the patterns of conflict that exist due to competing land uses. Attention is also paid to concrete governance approaches in protected areas against the background of competition for land and the question of how experience gained in protected areas can be transferred to ‚normal‘ landscapes. The paper also provides basic definitions relevant to the topic. Finally, from the perspective of various disciplines, the working group calls for policy and planning actors to support the sustainable development of protected areas in Germany. Here the focus is not only on a stringent strengthening of the status of protected areas on the federal level combined with appropriate administrative structures, but also on promoting improved quality assurance and quality development of the protected areas. Of further relevance to these calls for action is the field of tension between the necessity for strengthened process protection and the intensification of agriculture in the context of EU Common Agricultural Policy.
Keywords: Nature Protection; Biodiversity; Acceptance; Land Use Conflicts; Protected Areas